2018
DOI: 10.1126/science.aat7871
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin domains rich in inheritance

Abstract: Only certain histone posttranslational modifications qualify as being epigenetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 14 publications
5
140
0
1
Order By: Relevance
“…Perhaps this might seem contradictory to the prevailing notion of the histone mark as a repressor. However, the delayed change of the histone modification after transcriptional change is consistent with previous reports showing the same relationship upon global induction of cellular stimuli (Hosogane et al, 2013;Kashyap et al, 2011), and with the mechanistic property of the repressive state as an epigenetic memory (Reinberg and Vales, 2018). Also accumulative evidence has shown that PRC2 has almost no effect on gene expression in a certain context (Riising et al, 2014).…”
Section: The H3k27me3 Mark Reflects the Gene Expressionsupporting
confidence: 90%
“…Perhaps this might seem contradictory to the prevailing notion of the histone mark as a repressor. However, the delayed change of the histone modification after transcriptional change is consistent with previous reports showing the same relationship upon global induction of cellular stimuli (Hosogane et al, 2013;Kashyap et al, 2011), and with the mechanistic property of the repressive state as an epigenetic memory (Reinberg and Vales, 2018). Also accumulative evidence has shown that PRC2 has almost no effect on gene expression in a certain context (Riising et al, 2014).…”
Section: The H3k27me3 Mark Reflects the Gene Expressionsupporting
confidence: 90%
“…Genome function and cellular identity are maintained through the structural organization of chromatin domains that either facilitate or impede transcription. The presence of specific histone post-translational modifications (PTMs) within these chromatin domains not only correlate with a given transcription status, but also facilitate the formation of repressive chromatin structures that impact gene expression (Reinberg and Vales, 2018). In order to maintain the integrity of these gene expression programs through cell division, the molecular features defining these chromatin structures must be transmitted, rather than established anew.…”
Section: Introductionmentioning
confidence: 99%
“…For one, the mammalian Pc homologue CBX2, like HP1 proteins, can promote phase separation that is dependent upon amino-acids in CBX2 necessary for nucleosome fibre compaction (197,198). Second, the histone modifications H3K9me2/3 and H3K27me3 are diagnostic for HP1-and Pc-dependent domains/complexes respectively (Table 1) (199) and are used, inter alia, to define B-type compartmental domains (170). Given that H3K9me2/3 and H3K27me3 are the only histone modifications that are truly epigenetic (199) we suggest that the B-type compartmental domains generated by HP1-and Pc-dependent domains/complexes are epigenetic compartmental domains (ECDs) that drive the compartmentalisation seen in Hi-C maps in the same way that cytologically-visible compartmental segregation is driven solely by heterochromatin (178).…”
Section: "Epigenetic Compartmental Domains" (Ecds) and The Regulationmentioning
confidence: 99%
“…Pc-dependent domains/complexes respectively (Table 1) 199 and are used, inter alia, to define B-type compartmental domains 170 . Given that H3K9me2/3 and H3K27me3 are the only histone modifications that are truly epigenetic 199 we suggest that the B-type compartmental domains generated by HP1-and Pc-dependent domains/complexes are epigenetic compartmental domains (ECDs) that drive the compartmentalisation seen in Hi-C maps in the same way that cytologically-visible compartmental segregation is driven solely by heterochromatin 177 .…”
Section: "Epigenetic Compartmental Domains" (Ecds) and The Regulationmentioning
confidence: 99%